1987
DOI: 10.1063/1.339085
|View full text |Cite
|
Sign up to set email alerts
|

Orientation control of the silicon film on insulator by laser recrystallization

Abstract: Lateral impurity transport in silicon films on insulators during laser recrystallization Appl. Phys. Lett. 48, 356 (1986); 10.1063/1.96550 Strong 100 texture formation of polycrystalline silicon films on amorphous insulator by laser recrystallization Appl. Phys. Lett. 45, 854 (1984); 10.1063/1.95425Silicon thin films formed on an insulator by recrystallization

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…So far, every laser crystallization method to produce grain-boundary-free films at a temperature less than 450 • C has failed to control crystal orientations of the crystallized region, and conversely, every method to obtain preferentially-oriented films has failed to eliminate grain boundaries from the crystallized region. The observation of the grain boundaries after the delineation by Secco etching of the crystallized film reveals that the grain boundaries can be eliminated from a defined area in the CW-laser crystallization, if isotherms are modulated by beam shaping [26][27][28][29], stripe cap patterning [30,31], Si island patterning [32][33][34], or substrate patterning [35]. The idea of these methods is to make the temperature of the controlled crystal growth region less than that of the peripheral regions, to suppress the disturbance to the growth region from the random nucleation at the peripheral.…”
Section: Comparison Between Continuous-wave (Cw)-laser Lateral Crysta...mentioning
confidence: 99%
See 1 more Smart Citation
“…So far, every laser crystallization method to produce grain-boundary-free films at a temperature less than 450 • C has failed to control crystal orientations of the crystallized region, and conversely, every method to obtain preferentially-oriented films has failed to eliminate grain boundaries from the crystallized region. The observation of the grain boundaries after the delineation by Secco etching of the crystallized film reveals that the grain boundaries can be eliminated from a defined area in the CW-laser crystallization, if isotherms are modulated by beam shaping [26][27][28][29], stripe cap patterning [30,31], Si island patterning [32][33][34], or substrate patterning [35]. The idea of these methods is to make the temperature of the controlled crystal growth region less than that of the peripheral regions, to suppress the disturbance to the growth region from the random nucleation at the peripheral.…”
Section: Comparison Between Continuous-wave (Cw)-laser Lateral Crysta...mentioning
confidence: 99%
“…Even if a grain boundary happened to be formed in a central crystallized region, the grain boundary is swept outward with scan travel. However, it is difficult to realize the surface orientation control in addition to the grain boundary elimination by these isotherm modulations [29,31,34]. Yeh et al reported a 1 mm-long grain-boundary-free Si stripe of 4 µm-width, having {100}-orientation in surface normal and {320}-orientation in scan direction, by crystallization with a chevron-shaped CW laser beam and a 300 nm-thick SiO 2 cap [36]; however, they also reported orientation rotation with the scan travel in other scans at the same crystallization conditions in the same paper [36].…”
Section: Comparison Between Continuous-wave (Cw)-laser Lateral Crysta...mentioning
confidence: 99%
“…This problem is fundamental in pulse LILG and is unavoidable. In contrast in cw LILG, [10][11][12][13][14][15][16][17][18][19][20][21] laser scanning velocity is synchronized with the lateral growth velocity, so that the lateral grain can grow under a steady state. The main problem in cw-LILG is uncontrolled grain boundaries, which are approximately parallel to the laser scanning direction, 22) and grain boundaries, in addition to crystal orientation, are still the main factors affecting device deviation.…”
Section: Introductionmentioning
confidence: 99%
“…Several types of SOI structures have been previously investigated, such as lateral growth of amorphous Si 2, separation by implanted oxygen (SIMOX) 3 and direct wafer bonding 4,5. Problems associated with the above mentioned approaches include defect generation 6 , 7 control of regrowth orientation 8 , and uncertainty of the thickness of the insulating layer 5.…”
Section: Introductionmentioning
confidence: 99%